Abordagem investigativa da digestão e alimentação com estudantes do ensino médio - Gomes, Maria Angélica Muniz (2019)
This work observed the need to contextualize concepts related to the functioning of the human digestive system and to food education, a didactic sequence was produced with investigative activities about nutrition and digestion. The objectives of this didactic tool are to approach and disseminate these themes among the students of High School through investigative tasks, raise awareness about the importance of adequate nutrition and generate reflection on health and nutrition, as well as assisting in learning the digestive system. The didactic sequence provided more encouragement to the students and resulted in more interest, dedication and satisfaction, contributing to the construction of knowledge about the proposed topics. It is imperative to discuss healthy eating with students in a more contextual and effective way so that students understand that the results of a food change will be seen in various aspects of their lives. The product developed in this study offers students a knowledge about food and digestion that enables responsible food choices.